High-resolution modeling of meander neck cutoffs: laboratory and field scales - Li, Zhi; Mendoza, Alejandro; Abad, Jorge D.; Endreny, Theodore A.; Han, Bangshuai; Carrisoza, Eliseo; Dominguez, Ramon (Frontiers in Earth Science, 2023)
Meandering rivers are distinguished by their characteristic sinuosity, which is subject to modulation through channel cutoff, resulting in the formation of oxbow lakes within the abandoned meander loops. Throughout the evolutionary course of a river, these cutoffs establish a connection between the channel and floodplain systems, both crucial to maintaining the dynamic equilibrium of the river system. Nonetheless, the interactive dynamic between the channel and floodplain and its influence on the transient behavior of the channel's morphodynamics during a cutoff event are frequently reduced to simplistic representations in computational models. This study introduces a comprehensive numerical model that elucidates the adaptive processes of bed and planform during and subsequent to the inception of cutoff and oxbow lakes. The model is assessed through its application to a laboratory scale cutoff, before being employed to a real-world meandering river, specifically the Ucayali River in Peru, in order to gain understanding into channel development and the intricate patterns of planform dynamics following cutoff events. The model is able to capture the main modes of planform migration, translation and expansion for the case of the bend in the Ucayali River. During the neck cutoff, the model simulates the progression of erosional and depositional waves traveling in upstream and downstream directions respectively, underscoring the importance of incorporating both hydrodynamic and morphodynamic factors in characterizing the river dynamics associated with meander cutoffs.